Handbook of medical textiles - Bartels, V. T. (Woodhead Publishing, 2011)
With a rising population and the increasing range of textiles for medical products, the need to understand and improve medical textiles is gaining in importance. The Handbook of medical textiles provides an overview of the different types of medical textiles currently available as well as specific information on more specialised topics and applications. In part one, the types and properties of medical textiles are discussed, with chapters covering topics including reusable textiles, textiles for implants and textiles with cosmetic effects. Part two focuses on the interaction of textiles with the skin, examining key issues such as contact sensations, allergies and mechanical irritation. Chapters in part three provide information on the latest developments in textiles for hygiene and infection control, while part four provides a range of applications and case studies, including improvements in medical occupational clothing, medical filters and superabsorbent fibres. With its expert editor and contributions from some of the world's leading authorities, the Handbook of medical textiles is a standard reference for designers and manufacturers of medical textile products, as well as for biomaterials scientists and medical professionals. Explores the different types of medical textiles currently available as well as specific information on more specialised areas and applicationsChapters cover topics such as reusable textiles, textiles for implants and interaction of textiles with the skinIs a standard reference for designers and manufacturers of medical textile products, as well as for biomaterials scientists and medical professionals.
"The Textile Institute.'
Keywords: Biomedical materials.; Textile fabrics.; elektronické knihy; electronic books